Training transfer: the impact of employee characteristics and behavioural change on employee performance - Zainal, Artinah; Hashim, Rahmat; Mohd Shariff, Fadzilah (2011)
Establishing and maintaining relationship with customers is of paramount importance to success in tourism and hospitality industry. Frontline employees playa critical role in linking tourism and hospitality firms with customers and thus in maintaining long-term relationships (Kusluvan, 2003). Successful service firm have invested resources into programs in order to increase their employees' performance and job satisfaction (cf. Karatepe, Uludag, Menevis, Hadzimehmedagic, & Baddar, 2006). According to Singh (2000), frontline employees are still undertrained, underpaid, and overworked. In apparent recognition of this, tourism and hospitality managers need to seek effective ways to be able to enhance the performance and job satisfaction of frontline employees (Karatepe et al. 2006). Reviewing the marketing literature, there are extensive number of empirical studies that have been investigated the effects of various organizational variables on frontline employee or salesperson performance and job satisfaction (Brown & Peterson, 1994; G. A. Churchill, Jr., Ford, Hartley, & Walker, 1985). Nevertheless, less empirical attention has been paid to the effects of individual characteristics, and effort on performance (Brown &Petterson, 1994; Krishnan, Nanetemeyer, &Boles, 2002). This is also applicable in the tourism and hospitality literature, particularly, very little known about the effects of individual characteristics on frontline employee performance in tourism and hospitality literature. Moreover, research has not directly investigated how employees' characteristics effect on work performance.